Analytical study of the interaction between fatawa, shariah rulings, resolutions and conventional laws in contemporary Islamic finance in Malaysia with cross reference to the practices in Saudi Arabia, Pakistan and the Sudan - Md Nor, Mohd Zakhiri (International Shari’ah Research Academy for Islamic Finance (ISRA), 2010)
The objectives of this research are to examine the interaction between fatawa, resolutions, Shari'ah rulings and conventional laws in contemporary Islamic finance in the Malaysian conventional legal framework. This research will analyse the practices in Saudi Arabia, Pakistan and Sudan through comparative analysis and the lessons to be learned. Another objective is to examine the extent of consistency of current Islamic finance practices in Malaysia in the context of established classical legal frameworks and to propose recommendations to fatwa-issuing bodies, Shari'ah advisory bodies, dispute settlement agencies and executive governmental functionaries for better governance of Shari'ah in Malaysia.